Letter to Senator Edmund Muskie from Jane Tolmach and Adele Leopold - Jane Tolmach::::::; Adele Leopold:::::: (1971)
In this January 7, 1971 letter, Jane Tolmach and Adele Leopold invite U.S. Senator Edmund S. Muskie to be the speaker at the Key Women Award Party on January 16, 1971, at the Beverly Hilton in Los Angeles. The event honors women volunteers who worked for Democratic nominees in the 1970 campaign, and Muskie is praised for his key role in Democratic victories nationwide. They express hope that he and Mrs. Muskie can attend and note that they will follow up with his Washington office.